Amniotic membrane, a novel bioscaffold in cardiac diseases: from mechanism to applications - Rayat Pisheh, Hossein; Darvishi, Ahmad; Masoomkhah, Seyed Saeid (Frontiers in Bioengineering and Biotechnology, 2024)
Cardiovascular diseases represent one of the leading causes of death worldwide. Despite significant advances in the diagnosis and treatment of these diseases, numerous challenges remain in managing them. One of these challenges is the need for replacements for damaged cardiac tissues that can restore the normal function of the heart. Amniotic membrane, as a biological scaffold with unique properties, has attracted the attention of many researchers in recent years. This membrane, extracted from the human placenta, contains growth factors, cytokines, and other biomolecules that play a crucial role in tissue repair. Its anti-inflammatory, antibacterial, and wound-healing properties have made amniotic membrane a promising option for the treatment of heart diseases. This review article examines the applications of amniotic membrane in cardiovascular diseases. By focusing on the mechanisms of action of this biological scaffold and the results of clinical studies, an attempt will be made to evaluate the potential of using amniotic membrane in the treatment of heart diseases. Additionally, the existing challenges and future prospects in this field will be discussed.